2021
DOI: 10.1002/aisy.202100006
|View full text |Cite
|
Sign up to set email alerts
|

High‐Output Force Electrohydraulic Actuator Powered by Induced Interfacial Charges

Abstract: Herein, a novel soft actuator design is presented that simultaneously enables a high‐output force at a low operating voltage and an adjustable large normal displacement. The electrohydraulic actuator powered by induced interfacial charge (EPIC) uses the amplified electrostatic force when the surface charge‐inducing phenomenon of the polyvinyl chloride (PVC) gel and the geometrical gradient of the actuator are combined to reinforce the zipping motion of the liquid layer. This actuator produces a more than 50‐fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The resulting force by this pressure is usually referred to as an actuator's blocking force. [36,52] To validate this force stroke relation, we recorded the swelling of 2 mm thick SAP 37/1 discs (radius of 5.6 mm) in water without and with an external load (100 kPa) over a time of 8 h. From the stress-strain curve in Figure 4a, a 100 kPa load is expected to decrease the relative elongation to 1.2 ± 0.2. Figure 4b shows the measured increase in thickness over time.…”
Section: Swelling Characteristicsmentioning
confidence: 99%
“…The resulting force by this pressure is usually referred to as an actuator's blocking force. [36,52] To validate this force stroke relation, we recorded the swelling of 2 mm thick SAP 37/1 discs (radius of 5.6 mm) in water without and with an external load (100 kPa) over a time of 8 h. From the stress-strain curve in Figure 4a, a 100 kPa load is expected to decrease the relative elongation to 1.2 ± 0.2. Figure 4b shows the measured increase in thickness over time.…”
Section: Swelling Characteristicsmentioning
confidence: 99%
“…It was reported that the deformation of PVC-gel is caused by electrostatic force acting on the anode due to the accumulated plasticizer as the charge carrier 44,45 . With these merits, PVC-gel was employed in soft actuators [46][47][48] , haptic interfaces 49 , tunable lenses 50 , soft sensors 51 , and electric generators 52 . It is newly suggested that PVC-gel can be applied in heaters due to its mechanical, optical, and thermal functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, substantial efforts have been made in the development of soft robots, which exhibit conformable complex motions that ensure safe interactions between humans and robots. [1][2][3][4] By employing various actuation methods, [5][6][7][8][9][10][11] soft robots are able to perform a variety of bioinspired deformations, [4,[12][13][14] ranging from bending, [15][16][17][18] contraction, [19][20][21] to elongation. [22][23][24] However, despite these advances, rotation remains a persistent challenge in soft robots.…”
Section: Introductionmentioning
confidence: 99%